Produção de etanol de segunda geração no cenário brasileiro: identificação de fatores para a eficiência e viabilidade do processo - Caldeira, Gabriel Henrique Vicentin (Universidade Federal de São Carlos, 2025)
In the search for more sustainable alternatives for the global energy matrix, second-generation ethanol (2G) has emerged as a promising option, especially in Brazil, where sugarcane bagasse and other lignocellulosic biomass are abundant and can play a central role in the development of the bioeconomy. The production of 2G ethanol uses agricultural and industrial by-products, offering the advantage of not directly competing with the food chain, unlike first-generation (1G) biofuels. Lignocellulosic biomass is composed of cellulose, hemicellulose and lignin, of which cellulose and hemicellulose are composed of fermentable sugar monomers. To access the sugars present in lignocellulosic biomass, a pretreatment step is first required to break down the recalcitrant structure of the biomass, followed by enzymatic hydrolysis using cellulases and hemicellulases to release the sugars. This process can be conducted in different ways, such as SHF (separate hydrolysis and fermentation), SSF (simultaneous saccharification and fermentation), SSCF (simultaneous saccharification and co-fermentation) and BPC (consolidated bioprocessing). Additionally, the economic competitiveness of 2G ethanol is a key factor for its industrial implementation. In this context, this study examined the different ways of conducting the enzymatic hydrolysis and fermentation processes for ethanol production, with a special focus on the economic impact of each type of process, exploring the impact of enzyme concentration, the type of biomass used and other relevant analyses. First, a bibliometric analysis of the processes was performed using the VOSViewer® software and an extensive literature review to build the parameter database of the different processes. The data obtained were processed in Microsoft PowerBI® to build trend graphs to identify correlations. The results indicated that the optimization of the temperature, time, enzyme load, type of biomass and type of process factors are essential for the technical-economic improvement of ethanol production, especially the conduction of the process by BPC which, despite there still being little data and studies in the area, presented the most promising minimum ethanol selling price (MESP) (0.34 USD/L).
Second-generation ethanol production in the Brazilian scenario: identification of factors for process efficiency and viability
Keywords: Bioenergia; Etanol de segunda geração; MESP; Rotas de produção; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA